Do (outgroup) teachers always heighten anxiety and threaten stem students’ classroom outcomes? - Karunagharan, Jaya Kumar (2024)
Malaysia, along with the rest of the world, needs more Science, Technology, Engineering and Mathematics (STEM) literate professionals. However, the persistent gender gaps in STEM make it difficult to meet the demand and stand in the way of scientific and economic progress. Although minority group participation in education has improved over the years, generally, fewer ethnic minority and female students tend to pursue STEM-related fields. One prominent explanation is that there aren’t enough ingroup role models in STEM education to boost confidence in pursuing this profession, given the anxiety faced by underrepresented groups due to the stereotype that STEM is not for them. However, despite the positive effects of role models, these effects are disproportionate which suggests that there could be other factors that counter the inoculating effect of role models.